Penerapan Metode Gerakan untuk Meningkatkan Kemampuan Menghafal Hadis Pada Siswa Kelas I SDIT As-Syafi’iyah Kota Pekanbaru. Kota Pekanbaru: Indonesia - Syahri Ramadhan; Niswatul Kahasanah; Khusnul Khotimah (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This research was motivated by the low ability to memorize Hadith in grade I students of Integrated Islamic Elementary School as-SyafiiyahPekanbaru. This can be seen from the phenomenon and the initial test of students so that the results obtained are not as expected. The purpose of this study is to find out the application of Movement Methods to improve the appearance of Memorizing Hadith in Grade I Students in As-Syafi'iyah Integrated Islamic Elementary School in Pekanbaru city. This class action research uses the Kemmis and Taggart models. The subjects of this study were grade I students who numbered 22 students. The study consisted of two cycles. For this class action research to succeed properly without obstacles that interfere with the smoothness of the research, researchers compile the stages passed in class action research, namely: 1) planning, 2) implementation of actions, 3) observation, and reflection. Data on students' learning outcomes are collected using tests and observation manual sheets. Furthermore, the data is analyzed quantitatively and qualitatively. The results of this study explained that the application of the Movement Method can improve the ability to memorize Hadith in Grade I in The Islamic Primary School As-Syafi'iyah Pekanbaru City. This can be proven from the significant increase in cycle I which is with a percentage of 69.32% and achieved the expected completion rate in cycle II with a percentage of 80.68%.